Factors associated with psychological insulin resistance among patients with type 2 diabetes in China - Zhang, Shilong; Zhang, Xindan; Wang, Haipeng; Fan, Wenyu; Ma, Xingli; Song, Suhang; Zhang, Beibei (Frontiers in Endocrinology, 2024)
Objective The aim of this study was to understand the psychological insulin resistance status among Chinese patients with type 2 diabetes and investigate its associated factors in these patients. Methods A multi-stage stratified random sampling was performed to randomly select patients with type 2 diabetes from the eastern, central, and western regions in Shandong Province, China, and 660 valid questionnaires were collected. Psychological insulin resistance was assessed by the scale of My Opinion on Insulin (MOI). Factors associated with psychological insulin resistance were examined in a binary logistic model. Results Four-fifths of the patients with type 2 diabetes (82.1%) had psychological insulin resistance. Being female (OR = 1.770, 95% CI: 1.063–2.950, p < 0.05), having a monthly income of greater than 4,000 Renminbi (approximately $1,540) (OR = 0.444, 95% CI: 0.216–0.915, p < 0.05), living with type 2 diabetes for 11 years or more (OR = 0.387, 95% CI: 0.238–0.630, p < 0.05), self-rated poor health (OR = 1.706, 95% CI: 1.092–2.664, p < 0.05), and moderate discrimination against type 2 diabetes (OR = 1.924, 95% CI: 1.166–3.175, p < 0.05) were associated with psychological insulin resistance. Conclusions The prevalence of psychological insulin resistance among Chinese patients with type 2 diabetes is relatively high. Approaches are needed to address the issue of psychological insulin resistance of type 2 diabetes.